Condutas autolesivas e bullying em adolescentes de Sergipe - Santos, Luana Cristina Silva (2017)
Understanding the self-harm behavior can help to explain how difficult or easy is the engagement in risk behaviors, included that unhealty. We see that self-harm behavior and the bullying have emerged and researchers have been give attention for it, mainly at adolescence and in the scholar context, the place where we observe more prevalence of it. In this sense, we aimed to investigate the possible relationships between self-harm behaviors and bullying victimization at adolescents of Sergipe. We did three studies: first, a theoretical article that brings the concept, classification and description the self-harm behavior about the development phases, associated factors, diagnostic, treatment/intervention and prevention; second, a empirical article about social distribution of bullying at adolescentes of Sergipe; and third, the main study, a empiral article that investigated possible relationships between self-harm behavior and bullying, as well between self-harm behavior and sociodemographic perfil of a adolescent sample of Sergipe. Mainly, we add knowledge to the literature about self-harm behavior, what contributes for thematic studies because get together the literature findings. At second place, the screening of bullying in Sergipe confirmed the phenomenon prevalence with a rapid diagnostic scale and for this we can use this variable in the third study. At the end, we identified the self-harm occurrence, as well precipitators or reinforcement factors, being possible doing the classification by specific groups of population, our main objective.